Molecular evolution of PCSK family: Analysis of natural selection rate and gene loss - Najmeh Parvaz (Public Library of Science (PLoS), 2021)
Proprotein convertases subtilisin kexins are serine endoproteases, playing critical roles in the biological functions, including lipid, glucose, and bile acid metabolism, as well as cell proliferation, migration, and metastasis. Experimental studies have demonstrated the physiological functions of PCSKs and their association with diseases; however, studies on the evolutionary history and diversification of these proteins are missing. In the present research, a bioinformatics study was conducted on the molecular evolution of several PCSKs family members and gene loss events across placental mammalian. In order to detect evolutionary constraints and positive selection, the CodeML program of the PAML package was used. The results showed the positive selection to occur in PCSK1, PCSK3, PCSK5, and PCSK7. A decelerated rate of evolution was observed in PCSK7, PCSK3, and MBTPS1 in Carnivores compared to the rest of phylogeny, and an accelerated evolution of PCSK1, PCSK7, and MBTPS1 in Muridae family of rodents was found. Additionally, our results indicated pcsk9 gene loss in 12 species comprising Carnivores and bats (Chiroptera). Future studies are required to evaluate the functional relevance and selective evolutionary advantages associated with these modifications in PCSK proteins during evolution.